General and ocular symptoms in systemic lupus erythematosus (SLE) - Brydak-Godowska, Joanna (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
Systemic lupus erythematosus (SLE) is a chronic, immunologically mediated inflammatory connective tissue disorder with manifestations including various body organs (joints, pleura, pericardium, kidneys, brain, skin), caused by accumulation of immune complexes. According to epidemiological data SLE affects 0.12% of the population worldwide, while in Poland the number of reported cases is c. 60 000 – 80 000. SLE may also involve the eye. Anterior segment findings include keratoconjunctivitis sicca, keratitis and scleritis. Retinal manifestations of SLE are cotton wool spots, hemorrhage and vasculitis. The ARA (American Rheumatism Association), criteria are used in establishing the diagnosis of SLE. Although the ocular symptoms are not included in the ARA criteria, they may be initial findings and precede other manifestations of SLE.